Resistance is Our Heritage: An Archive of Survival and Efforts to Resist Gentrification in Little Jamaica. - Pereira, Marcus Thomas (University of Waterloo, 2025)
Rooted in my experience as a community member and organizer, this thesis documents the history and resistance of Little Jamaica in Toronto as it continues to face the impacts of gentrification and displacement. Using Black archival practice as my methodology, I draw from oral histories, protest materials, community reports, and digital media to center the voices and experiences of residents, business owners, and activists. Grounded in the framework of racial capitalism, this research understands gentrification as part of a longer history of displacement, extraction, and state neglect targeting Black communities. It traces the development of Little Jamaica through Caribbean migration and examines how planning interventions—particularly the Metrolinx Light Rail Transit construction—have intensified economic pressure, disrupted local business, and contributed to cultural erasure. By amplifying community narratives and mobilizing knowledge for advocacy, this thesis not only documents the fight to preserve Little Jamaica’s cultural identity, but also contributes to broader discussions on gentrification, displacement, and resistance. It highlights the everyday strategies, care networks, and collective organizing that continue to sustain the neighborhood. Ultimately, it seeks to equip residents with knowledge and tools for organizing while challenging dominant narratives of progress and revitalization. At its core, this work affirms that the fight for Little Jamaica is ongoing—and that resistance has always been part of its story.
Keywords: gentrification; toronto; caribbean; displacement; resistance; little jamaica